PENGARUH FUNGSI KEPEMIMPINAN, KOMPETENSI, DAN BUDAYA ORGANSIASI TERHADAP KINERJA PEGAWAI PADA DIREKTORAT JENDERAL ENERGI BARU, TERBARUKAN DAN KONSERVASI ENERGI (DJEBTKE) - Manik, Ester; Coenraad, Dhea Perdana (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2021)
The research objective was to determine the function of leadership, competence, and organizational culture on employee performance. Descriptive research methods of verification with data analysis techniques using Path Analysis. Total respondents 127 employees denagan stratifield random sampling technique. The results showed there is a significant influence between the functions of leadership, competence, and organizational culture on employee performance either partially or simultaneously. As for competence has a direct effect of 20.6 %, the function of leadership has a direct effect of 17.2 % and direct influence of organizational culture by 4.4 %. Total overall effect is 72.6 % whereas the effects of other factors were not examined on the performance of 27.4 %. Keywords: function of leadership; competency; organizational culture; performance